PENGARUH LIDAH BUAYA DAN MADU TERHADAP PENYEMBUHAN LUKA DIABETIK PADA PASIEN DIABETES MELLITUS: DIABETES MELLITUS - Puspitosari, Dewi Retno; Nuridayanti, Anik; Wahdi, Achmad; Jayanti, Eka Ama Putri (WELL BEING, 2021)
Diabetes mellitus is a chronic disease caused by the pancreas not being able to produce insulin, resulting in an increase in blood sugar levels. One of the complications is diabetic foot ulcers. Wound treatment using aloe vera and honey can help heal diabetic wounds. The purpose of this study was to determine the effect of wound care using aloe vera and honey on diabetic wound healing in patients with diabetes mellitus at the Griya Husada Clinic, Kediri City. The research design used Pre-Experiment with One Group Pre-Postest Design. The study population was all patients with diabetes mellitus as many as 20 respondents who were taken by total sampling technique. The results of the study obtained degenerated wounds which eventually regenerated 2 respondents (10%), regenerating wounds that had healed tissue 5 respondents (25%). Analysis of the data with Wilcoxon found differences before and before wound care (p = 0.008 <0.05), then Ho was rejected and Ha was accepted. Therefore, there is an effect of wound care using aloe vera and honey on diabetic wound healing in patients with diabetes mellitus at the Griya Husada Clinic, Kediri City. It is suggested that aloe vera and honey can be applied in wound care to speed up the healing process in diabetic wounds. Keywords: Aloe Vera, Honey, Diabetic Wound.